Pengolahan Bahan Pustaka Keislaman dan Umum di Perpustakaan Museum Al-Qur’an melalui Kegiatan Katalogisasi dan Pelabelan Buku - Siti Mardiana Harahap; Era Asria Harahap; Reza Pahlevi; Reski Gosali; Husnel Anwar (Pusat Riset dan Inovasi Nasional, 2024)
Library material processing is an essential activity in library management to support collection organization and facilitate users’ access to information. The Library of the Museum of the History of the Qur’an of North Sumatra possesses a diverse collection of materials, including Islamic books and general books; therefore, a well-planned and systematic collection processing system is required. This internship activity aims to describe the process of processing Islamic and general library materials through cataloging and book labeling activities at the Library of the Museum of the History of the Qur’an of North Sumatra. The method used in this internship was a descriptive qualitative approach, with data collection techniques including observation, documentation, and direct practice in the processing of library materials. The results of the internship indicate that cataloging and book labeling play a significant role in creating organized collections, facilitating information retrieval, and supporting the effectiveness of library services. Thus, processing library materials through cataloging and labeling constitutes a strategic effort to enhance the quality of collection management at the Library of the Museum of the History of the Qur’an of North Sumatra.